(untitled) (Kairaranga, 2018)
Children’s challenging behaviour in classrooms can have negative effects on students and teachers. The New Zealand government is funding Incredible Years Teacher (IYT) professional learning and development (PLD) to provide teachers with classroom management skills to manage young children’s challenging behaviour. This research explored how teachers incorporated IYT into their practice, and the factors supporting or hindering sustained implementation. The qualitative approach of interpretive description was used to guide in-depth interviews with 12 teachers and other education professionals. The thematic analysis illuminated the variation in how teachers implemented IYT. Overall, teachers with more support deeply embedded IYT and sustained its incorporation in their practice.